Voices from the Field: English Education Students’ Perceptions of Research Readiness After Project-based Blended Learning Experiences - Sofiana, Nina; Hartono, Rudi; Wahyuni, Sri (Journal of English Teaching and Learning Issues, 2025)
Research competence is a key requirement for pre-service English teachers, yet its development remains a challenge. Project-Based Blended Learning (PjBBL), known for promoting engagement and autonomy, holds potential to address this issue. However, its influence on students’ research readiness is still underexplored. This study investigates English education students’ perceptions of their research readiness after engaging in PjBBL. Using a mixed-methods approach, data were collected through surveys, interviews, and focus group discussions with undergraduate students enrolled in a research methods course. Findings indicate that PjBBL enhances foundational research skills, critical thinking, and collaboration but presents challenges in advanced data analysis, time management, and resource accessibility. The study underscores the need for structured guidance, resource support, and training in research methodologies. Future research is encouraged to explore longitudinal impacts of PjBBL on research competence and to examine its integration with digital tools for advanced data analysis and academic writing.